Indiscipline in school institutions: social, political and historical aspects in the conception of pedagogues - Leite, Tuanny Cavalcanti; Fonseca, Géssica Fabriely; Brito, Max Leandro de Araújo (Revista Hipótese, 2019)
The aim of this study is to analyze conceptions of pedagogues about the social, political and historical aspects of school indiscipline in children 's education and elementary education. This is a qualitative research. As results presents conceptions of pedagogues about the behavior of children in school and the meanings attributed to the notion of discipline or indiscipline. The study concludes that in the conceptions of the pedagogues there is convergence for the responsibility of the family and the teachers.
Keywords: Discipline; Schools; Teaching